2000
DOI: 10.1056/nejm200004063421402
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Treatment in Children with Philadelphia Chromosome–Positive Acute Lymphoblastic Leukemia

Abstract: Unlike the usual type of all, Ph-positive ALL is associated with a poor prognosis. Nevertheless, in some patients with favorable prognosis features, the disease can be be controlled by intensive chemotherapy. Transplantation of bone marrow from an HLA-matched related donor is superior to other types of transplantation and to intensive chemotherapy alone in prolonging initial complete remissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
341
4
10

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 532 publications
(369 citation statements)
references
References 35 publications
14
341
4
10
Order By: Relevance
“…15,33,65 The percentage of patients found prednisone resistant may vary, but the prognosis is uniformly inferior to that of the corresponding patients with PGR. PPR can be used to adapt treatment intensity, 17,21,32 to identify HR subsets of Ph þ ALL 65,66 and to target alloSCT to very-high-risk subgroups of T-ALL. 24 (6) The role of alloSCT in first CR is limited to very-high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…15,33,65 The percentage of patients found prednisone resistant may vary, but the prognosis is uniformly inferior to that of the corresponding patients with PGR. PPR can be used to adapt treatment intensity, 17,21,32 to identify HR subsets of Ph þ ALL 65,66 and to target alloSCT to very-high-risk subgroups of T-ALL. 24 (6) The role of alloSCT in first CR is limited to very-high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…3,16 Of the 32 patients, 6 were considered high-risk (WBC4100 k, any age), 8 low-risk (WBCo50 k, ageo10 years) and the remaining 18 patients were intermediate-risk (WBCo100 k, any age). Fifteen patients received imatinib therapy either pre-or post-HCT (9 pre-HCT, 2 pre/ post-HCT, 2 post-HCT and 2 pre-HCT and at relapse) comprising the imatinib group, whereas the remaining 17 patients either never received imatinib (n ¼ 11) or received it only at the time of relapse post-HCT (n ¼ 6) were the nonimatinib group (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Disease-free survival (DFS) using standard chemotherapy is reported to be 25-30% in children and less than 20% for adults. 3 Earlier studies have shown that allo-hematopoietic cell transplant (HCT) from a matched-related donor decreases relapse rates, resulting in improved DFS to 40-60%. [4][5][6][7] At the gene level, the Ph þ chromosome is created by a translocation of the 5 0 portion of the bcr gene to the kinase domain of the abl gene, resulting in a novel fusion protein with unregulated tyrosine kinase (TK) activity.…”
Section: Introductionmentioning
confidence: 99%
“…3 In a retrospective analysis, children with translocation t(9;22) undergoing SCT from an HLA-identical sibling donor achieved 65% EFS, which is significantly better than the outcome from chemotherapy, 25% EFS. 4 Fewer relapses among the SCT recipients accounted for the improved outcome. More recent prospective multi-institution clinical trials corroborate the advantage of SCT.…”
Section: Sct In First Remissionmentioning
confidence: 99%